Kemampuan Guru dalam Implementasi Contextual Teaching and Learning (CTL) untuk Pembelajaran Pendidikan Kewarganegaraan dan Pengetahuan Sosial - Widayati Widayati; Suminah Suminah; Suwarti Suwarti (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
This descriptive-evaluative study aims at describing teachers' competence in implementing Contextual Teaching and Learning (CTL) in Civics and Social Education. Involving 32 fourth-grade teachers, this study employed questionnaires and documentation in collecting the data. The results of descriptive analyses indicate that teachers' competence was of fair category. This fair category applies to all these aspects: CTL development, teaching-strategy selection, application of the seven CTL elements, and CTL-procedure implementation. The teachers appeared not to have difficulty implementing CTL.